Autophagy: A Versatile Player in the Progression of Colorectal Cancer and Drug Resistance - Manzoor, Shaista; Muhammad, Jibran Sualeh; Maghazachi, Azzam A.; Hamid, Qutayba (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is among the topmost malignancies for both genders. Despite the high incidence rate and advances in diagnostic tools, treatment in many cases is still ineffective. Most cancerous lesions in CRC begin as benign, followed by the development of invasive forms and metastases. The development of CRC has been linked to defects in autophagy, which plays both a pro-and anti-tumor role and is mainly context-dependent. Autophagy suppression could enhance apoptosis via p53 activation, or autophagy also promotes tumor progression by maintaining tumor growth and increasing resistance to chemotherapy. Autophagy promotes the invasion and metastasis of CRC cells via increased epithelial-mesenchymal transition (EMT). Moreover, dysbiosis of gut microbiota upregulated autophagy and metastasis markers. Autophagy responses may also modulate the tumor microenvironment (TME) via regulating the differentiation process of several innate immune cells. Treatments that promote tumor cell death by stimulating or inhibiting autophagy could be beneficial if used as an adjunct treatment, but the precise role of various autophagy-modulating drugs in CRC patients is needed to be explored. In this article, we present an overview of the autophagy process and its role in the pathogenesis and therapeutic resistance of CRC. Also, we focused on the current understanding of the role of the EMT and TME, including its relation to gut microbiota and immune cells, in autophagic manipulation of CRC. We believe that there is a potential link between autophagy, TME, EMT, and drug resistance, suggesting that further studies are needed to explore this aspect.